Respostas hematológicas em tuvira após anestesia com diferentes concentrações de óleo de cravo - de Pádua, Santiago Benites [UNESP]; Ventura, Arlene Sobrinho; Satake, Fabiana; Ishikawa, Márcia Mayumi; Hisano, Hamilton; Rotta, Marco Aurélio; Arantes, Flávio Cese [UNESP] (My University, 2012)
The hematological responses in tuvira (Gymnotus aff. inaequilabiatus) after clove oil anesthesia at different concentrations were evaluated in this study. Fish (n = 25) with average length of 26.8 ± 2.4 cm and weighing 94.4 ± 23.6 g were separated in five groups composed with five animals each and submitted individually to respective concentrations of clove oil: 40, 80, 120, 160 and 200 mg L-1. After anesthetic recuperation, the blood samples collection were performed, as well as complete hemogram. The results were submitted to analysis of variance, Tukey test (P<0.05) and Sperman's correlation analysis. There was an increase (P<0.05) on hematocrit, red blood cells count, thrombocytes count and in the values of neutrophils with increasing of clove oil concentrations. In addition, positive correlation (P<0.05) were observed on total leukocytes, as well as negative linear correlation (P<0.05) for mean corpuscular hemoglobin concentration (MCHC). The clove oil anesthesia on tuvira cause hematological changes with an effect dose-dependent. These changes should be considered mainly in future studies designed to establish the reference values of hematologic variables for this specie.
Hematological responses in tuvira after clove oil anesthesia at different concentrations
Keywords: Alternative anesthetic; Eugenol; Fish hematology; Gymnotus aff. inaequilabiatus; Live bait